MEDIA PEMBELAJARAN BUDIDAYA TANAMAN PARE PADA SMK PERTANIAN PEMBANGUNAN NEGERI JAMBI - Adhiatma, Novri Novri (Lembaga Penelitian Dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2017)
Abstract -  Learning technology has the main purpose to identify and solve learning problems. The learning problem-solving is very important because it is associated with an increase in the quality of learning. This increase can be reached by direct learning activities on three important aspects, namely effectiveness, efficient, and attractiveness. Especially at Vocational High School of Agricultural Development (SMK- PP) of Jambi yet available teaching materials that really is designed specifically for students learning SMK Negeri-PP Jambi. Learning materials have so far only in the form of a text book whose title manifold and skills unit package. Therefore, it was felt necessary to develop multimedia-based learning media. From the results of the study concluded that the information generated from the use of multimedia can be applied as a medium of teaching, because based on instructional materials in accordance with the existing material on-PP SMK Negeri Jambi. Keywords: Design, Information Systems, Distribution.